Ṭhākurera galpakathā - Modaka, Anitendu (Rā' Prakāśana, 2023)
Stories based on speeches of Ramakrishna, 1836-1886, Indian Hindu mystic and saint on philosophy of life.
Short stories
Keywords: Life; Fiction.; Hindu philosophy; Fiction.; Short stories; Bengali.